Insider trading restrictions and real earnings management: International evidence - WANG, Jiwei (Institutional Knowledge at Singapore Management University, 2022)
We examine the implications of insider trading restrictions on firms’ real activities earnings management in an international setting. Using a sample of 28 countries over the period from 1992 to 2007, we find evidence that is supportive of the substitution hypothesis, in that managers have incentives to substitute accruals earnings management for real activities earnings management. This effect is found to be more pronounced for firms in countries with more restrictive insider trading regulation. Our result is robust to alternative measures of real activities earnings man- agement and insider trading restrictions, alternative sub-samples, alternative regression specifi- cations, and controlling for endogeneity. In addition, we find that the positive association between insider trading restrictions and the substitution effect is more prominent for firms in countries with strong institutional infrastructure. Overall, our results are important in high- lighting the role of insider trading restrictions in shaping corporate financial reporting policies. In particular, we find strong evidence to suggest that the extent of restriction of such laws influence managerial incentives to engage in earnings manipulation through real activities.